Stunning from sains and Islamic perspective - Fiki Husna (Universitas Airlangga, 2021)
In 2012 the need for meat for consumption or industrial materials in Indonesia reached 484,000 tons and increased to 686,270 tons in 2019. The high demand for meat causes the intensity of slaughter to also increase so that the existence of slaughterhouses is very necessary. In the implementation process, RPH must pay attention to several aspects so that the quality of the meat produced is good, clean and the meat is halal. In the context of the codification of Islamic law (fatwa) in Indonesia, stunning is one of the important studies. This is evidenced by the fatwa of the MUI number 12 of 2009 concerning Halal Beef Certification Standards. This fatwa is motivated by several things, namely the practice of slaughtering animals in Islam must follow the provisions of Islamic law and in the implementation of the slaughter process many use modern equipment in line with technological developments, so that there are various models of cutting and processing that raise questions about the suitability of the implementation of slaughtering with Islamic law. The enactment of the Fatwa of the MUI number 12 of 2009 concerning Halal Slaughter Certification Standards by the Fatwa of the MUI on Mechanical Slaughter of Animals on October 18, 1976, the decision of the Coordination Meeting of the Fatwa Commission and LPPOM MUI and the Indonesian Ministry of Religion, on May 25, 2003, in Jakarta, Fatwa of the MUI Number 4 of 2003 concerning Standardization of Halal Fatwas; Results of the Decision of the Ulama Ijtimak of the Indonesian Fatwa Commission II in 2006 at the Gontor Ponorogo Islamic Boarding School on Critical Issues in Halal Auditing; The results of the Working Group Meeting of the ICU Fatwa Commission for Food, Drugs and Cosmetics and the ICU LPPOM Team on November 12, 2009. This fatwa resulted in a decision, one of which was related to stunning. Stunning to simplify the slaughtering process is legal, provided that: (1) Stunning only causes the animal to faint temporarily, does not cause death or permanent injury; (2) aims to facilitate slaughter; (3) its implementation as a form of ihsan, not animal torture